Manipulative and manual therapies in the management of patients with prior lumbar surgery: A systematic review. (February 2021) - Daniels, Clinton J.; Cupler, Zachary A.; Gliedt, Jordan A.; Walters, Sheryl; Schielke, Alec L.; Hinkeldey, Nathan A.; Golley, Derek J.; Hawk, Cheryl
Abstract: Background and Purpose: Pain and disability may persist following lumbar spine surgery and patients may subsequently seek providers trained in manipulative and manual therapy (MMT). This systematic review investigates the effectiveness of MMT after lumbar surgery through identifying, summarizing, assessing quality, and grading the strength of available evidence. Secondarily, we synthesized the impact on medication utilization, and reports on adverse events. Methods: Databases and grey literature were searched from inception through August 2020. Article extraction consisted of principal findings, pain and function/disability, medication consumption, and adverse events. Results: Literature search yielded 2025 articles, 117 full-text articles were screened and 51 citations met inclusion criteria. Conclusion: There is moderate evidence to recommend neural mobilization and myofascial release after lumbar fusion, but inconclusive evidence to recommend for or against most manual therapies after most surgical interventions. The literature is primarily limited to low-level studies. More high-quality studies are needed to make recommendations. Highlights: Three adequately powered randomized clinical trials investigated manual and manipulative therapy (MMT) after lumbar surgery. There is moderate evidence that inpatient neural mobilization does not improve outcomes after lumbar surgery. Low-level literature is suggestive of MMT being beneficial following lumbar surgery. There is inconclusive evidence to recommend for or against most MMT after most surgical interventions. The included studies did not adequately report on the impact of MMT on medication use or the incidence of adverse events.